Implementation of AI in Smart Logistics Based on Mobile Technologies - Svetlana Zemlyak; Irina Nozdreva; Svetlana Sivakova (International Journal of Interactive Mobile Technologies (iJIM), 2024)
These days, transport and logistics are undergoing a major transition due to the introduction of smart technologies (STs). STs use data science and artificial intelligence (AI) technologies, like big data and machine learning, to develop cognitive awareness of an object with the help of IoT and blockchain-based information and communication technologies. Currently, several ST applications have shown promise in raising the efficacy and efficiency of diverse transport and logistical systems. Furthermore, the modeling challenges posed by these new, cutting-edge technologies to conventional optimization techniques provide a wealth of fresh research opportunities for the development of novel optimization procedures in the field of logistics and transportation studies. The most effective system was discovered to be the human-AI one. The ultimate objective is to empower users with more knowledge and encourage safer, more organized, and “smarter” usage of transportation networks on mobile technologies. The Internet of Things (IoT) offers countless prospects for improved transportation management and new services related to logistics and data integration.